PERBEDAAN PENGARUH LATIHAN PASSING MENGGUNAKAN TARGET DAN LATIHAN PASSING BERPASANGAN TERHADAP KEMAMPUAN PASSING PADA SEKOLAH SEPAK BOLA (SSB) PUTRA MOJOSONGO CLUB TAHUN 2020 - Muhammad Khoirul Huda; Nuruddin Priya Budi Santoso; Agustanico Dwi Muryadi (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2021)
The objectives of this study are: (1) To determine the effect of training through the use of targets on soccer ability. (2) Knowing the effect of pair training on abilities through soccer games. (3) Knowing the difference in effect between using targets and pair training on passing abilities. The research method used is the experimental method. The subjects of this study were athletes of the SSB Putra Mojosongo Club which can accommodate 20 athletes. The data test method used is to use a passing accuracy test called a short passing test from a distance of 10 meters towards the target goal which has a width of 1 meter, which functions as a means of obtaining data. Based on the results of data analysis: (1) there is a significant effect between passing training using targets on the passing accuracy of the SSB Putra Mojosongo Club altet. This statement states with paired t-test results with a p-value <0.05 (p-value = 0.000). (2) there is a significant effect between the under-passing practice on the passing accuracy of the SSB Putra Mojosongo Club athletes. This is shown based on the results of the paired t test with a p-value <0.05 (p-value = 0.008). (3) the existence of an effect between target training and paired training on passing accuracy at SSB Putra Mojosongo altet. This is known through the unpaired test results with a p-value <0.05 (p-value = 0.011). In the percentage increase in the ability of each group, it is known that the passing training group using the target has an increase of 63.64% while the paired passing training group only experienced an increase of 25.64%.